2002
DOI: 10.1002/jca.10021
|View full text |Cite
|
Sign up to set email alerts
|

Mononuclear cell collection in patients undergoing extra‐corporeal photo‐chemotherapy for acute and chronic graft‐vs.‐host‐disease (GvHD): Comparison between COBE Spectra version 4.7 and 6.0 (AutoPBSC)

Abstract: A constant improvement in the performance of blood cell separators has been observed in recent years, allowing better yields in peripheral blood stem cell collection (PBSC) either from healthy donors or for autologous purposes. Nevertheless, to our knowledge, no reports on the efficiency of mononuclear cell (MNC) collection in patients undergoing extra-corporeal photochemotherapy (ECP) for graft-vs.-host-disease (GvHD) have been published. We retrospectively investigated the efficiency of 167 MNC collections p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
33
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 25 publications
5
33
1
Order By: Relevance
“…Perseghin et al [38] reported superior mononuclear cell (MNC) collection (p < 0.5) and less platelet contamination with the COBE software version 6 compared to version 4.6. Data were collected from 109 patients with GVHD treated using version 4.6 and 58 with version 6.…”
Section: Discussionmentioning
confidence: 99%
“…Perseghin et al [38] reported superior mononuclear cell (MNC) collection (p < 0.5) and less platelet contamination with the COBE software version 6 compared to version 4.6. Data were collected from 109 patients with GVHD treated using version 4.6 and 58 with version 6.…”
Section: Discussionmentioning
confidence: 99%
“…Pediatric experience with ECP for GvHD (to date, results on about 100 children treated are available) has mainly been reported by Italian [1][2][3][4][5][6][7][8][9] and French [10][11][12][13][14][15] groups. Most of this has been in the form of case reports or small series.…”
Section: Graft-versus-host Diseasementioning
confidence: 99%
“…2,4,6,8,9,11,14,15,17 In 73% of them, improvement was observed, with addition of ECP to their immunosuppressive regimen. A maximal response was observed after 10-15 ECP (1-2 months of treatment).…”
Section: Graft-versus-host Diseasementioning
confidence: 99%
See 2 more Smart Citations